Fingerprinting of ruby and sapphire gemstones through Fourier-transform infrared (FTIR) methodologies - A. Soares de Sousa; E. M. C. Gomes; L. Bayés-García; A. Di Mariano; M. Garcia-Valles (European Journal of Mineralogy)
Gemstones have significant economic, cultural, and artistic value. Advances in the treatment and production of synthetic gemstones create the need for more precise identification methods to distinguish natural stones from their synthetic and treated counterparts. Fourier-transform infrared (FTIR) spectroscopy, a non-destructive technique, is widely employed in advanced gemological analysis. In this study, 25 rubies and sapphires (natural, synthetic, and treated) from the Gemology School of the University of Barcelona were analysed using standard gemological instruments and FTIR spectroscopy. Distinct spectral fingerprints were identified for different categories and treatments. Untreated natural stones showed a band at 3230 cm−1 (with an additional peak at 3310 cm−1 in sapphires), whereas Verneuil specimens showed peaks at 3185, 2230, and 3310 cm−1 (with this last peak being more intense the one at 3310 cm−1 in sapphires), and flux specimens showed a 3310 cm−1 band. Regarding treated gemstones, diffusion-treated samples showed a faint band centred at 3310 cm−1; the glass-filled ones exhibited characteristic bands at 2250, 2600, and 3300 cm−1; and the treated Verneuil ruby showed a band centred at 3310 cm−1. These spectral fingerprints can be used to distinguish between natural, synthetic, and treated rubies and sapphires and contribute to existing databases, allowing for simpler and faster gemological analysis in future studies.